Artificial Intelligence and the Human Mind: Cognitive Psychology in the Age of Machines - Shahana Nadeem (`, 2025)
This article investigate the connection of artificial intelligence (AI) and human cognition, focusing on the implications of AI tools on cognitive psychology, human behavior, and decision-making processes. With the increasing use of AI in daily life, significant changes are occurring in how humans engage with cognitive tasks such as memory, problem-solving, and decision-making. AI systems, such as virtual assistants, predictive algorithms, and automated tools, offer considerable advantages by offloading cognitive load and improving efficiency. However, this integration raises concerns about the potential for cognitive dependency, where individuals may become overly reliant on AI, thereby diminishing critical thinking, memory retention, and overall cognitive abilities. The article examines key cognitive theories, including Cognitive Load Theory, the Extended Mind Hypothesis, and Dual-Process Theory, to interpret the effects of AI on human cognition. It also discusses the ethical considerations related to autonomy, trust, and dependency on AI systems. Furthermore, the paper highlights the implications of AI in various sectors such as education, workplace productivity, and mental health, emphasizing the need for a balanced approach that ensures AI complements human cognitive capabilities without undermining essential cognitive skills. The discussion extends to how AI challenges traditional definitions of intelligence, suggesting a need for new frameworks that incorporate human-AI interactions and their cognitive effects. The findings suggest that while AI offers significant cognitive enhancements, it is crucial to address the risks of over-reliance and ensure that AI remains a tool that augments human cognition rather than replacing it. Keywords: Artificial Intelligence, Cognitive Psychology, Cognitive Load Theory, Extended Mind Hypothesis, Dual-Process Theory, Cognitive Dependency, Human-AI Interaction, Ethics, Autonomy, Mental Health